Validation of Kogan's attitudes towards old people scale and an assessment of primary care level personnel attitudes towards the elderly - Sampén Celis, José Daniel (2012)
Introduction: A negative disposition influences the attitudes of health care professionals, since this is often based on erroneous assumptions about the usefulness of chronological age as a functional marker or with respect to elderly persons' ability to contribute to society. Material and Method: This is a study for validating an instrument, the Kogan's attitudes towards older people, and to determine attitudes towards the elderly in primary health care personnel in Tumbes. Results: A language validation was performed, the instrument was assessed by specifically appointed raters, and its reliability was also determined. Finally, the validated survey was administered to primary health care workers in Tumbes Health Direction. A 0,81 concordance coefficient (kappa) between translators and re-translators was found. The validity of the instrument was estimated on the basis of the assessment performed by the five aforementioned raters who reviewed every item. The coincidence value found was 84 %, and the reliability of the instrument was determined using the Cronbach alpha coefficient, which was 0,82. Two hundred health care workers were interviewed, and a positive attitude towards the elderly was found in 59% (118) of all surveyed persons. Conclusions: An instrument for measuring attitudes toward the elderly was validated. It was found that 59% of primary health care personnel had positive attitudes toward the elderly.